Geguritan Rare Kumara: Kajian Filsafat Pendidikan - Dharma, I Wayan Yudhasatya; Yusi Armini, Ni Wayan (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2025)
Geguritan Rare Kumara (GRK) is one of the many Balinese Purwa literary cases that are often sung on various occasions by the Balinese people. Like other Balinese literary cases, of course, GRK has noble values ​​in each verse of its pupuh. GRK is one of the sources of knowledge for the Balinese people in sharing life disciplines. However, the paradigm of the Balinese people has changed little by little, globalization has changed the perspective and also the way of life of the Balinese people today. The problems related to GRK gave birth to two problem formulations related to the functions and values ​​contained in GRK based on the study of educational philosophy. In general, the purpose of this study is to explore and reveal the nature of education contained in the Geguritan Rare Kumara (GRK) text.To explain the above problems, the author uses a qualitative research type. The data sources in this study are direct sources (primary) obtained in the field as a result of observations and scrutiny of GRK. While indirect sources (secondary) can be obtained through books, articles, written documents, and so on from libraries or other places. Primary and secondary sources can be combined or cross-checked to obtain data that is truly accurate and accountable. Data collection used here includes document and literature studies. After the data is obtained, it is analyzed by reducing, then presenting the data, and drawing conclusions.From the research conducted, findings related to the function of GRK based on the study of educational philosophy include as a medium to build intelligence as well as awareness and self-control. Next, related to the values ​​contained in GRK based on the study of educational philosophy, it was found that the aspects of these values ​​include the values ​​of independence, ethical values, and values ​​of responsibility. All of these findings were analyzed based on fundamental values ​​related to the aspects of education. In several verses of the pupuh analyzed through the research process, elements were found that were identical to these findings. So it can be concluded that GRK is one of the Balinese case literature texts that is full of educational values ​​in it. Keywords: Geguritan Rare Kumara, Philosophy of Education